Video-based Education Ethnography Project - Lori Goodson; F. Todd Goodson; David S. Allen (The Advocate, 2016)
This article chronicles the development of a video-based ethnography project documenting daily life in a Kansas elementary and a secondary classroom. The project, which took nearly two years of planning, allows a direct link to two classrooms approximately 250 miles away to provide a virtual field experience for undergraduates and a wide array of research possibilities for faculty. Since its first semester in spring 2016, it now enables students to see the daily actions of an elementary teacher and a secondary math teacher in a live classroom setting, and various faculty and graduate student research projects are currently under way.